2017
DOI: 10.1111/cla.12205
|View full text |Cite
|
Sign up to set email alerts
|

Weighted parsimony outperforms other methods of phylogenetic inference under models appropriate for morphology

Abstract: One of the lasting controversies in phylogenetic inference is the degree to which specific evolutionary models should influence the choice of methods. Model‐based approaches to phylogenetic inference (likelihood, Bayesian) are defended on the premise that without explicit statistical models there is no science, and parsimony is defended on the grounds that it provides the best rationalization of the data, while refraining from assigning specific probabilities to trees or character‐state reconstructions. Author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
377
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 337 publications
(388 citation statements)
references
References 95 publications
(318 reference statements)
6
377
1
4
Order By: Relevance
“…Goloboff et al . () have criticized this approach to simulating morphology‐like datasets on the basis that our generating trees encompass only contemporaneous taxa, assume that evolutionary rates are constant across time and the tree, and that our measure of biological realism, the spread of homoplasy exhibited by datasets, is inadequate. However, our experiments do not attempt to simulate non‐contemporary taxa or address the problem of missing data, qualities of palaeontological data that are of a level of complexity that is beyond the current debate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Goloboff et al . () have criticized this approach to simulating morphology‐like datasets on the basis that our generating trees encompass only contemporaneous taxa, assume that evolutionary rates are constant across time and the tree, and that our measure of biological realism, the spread of homoplasy exhibited by datasets, is inadequate. However, our experiments do not attempt to simulate non‐contemporary taxa or address the problem of missing data, qualities of palaeontological data that are of a level of complexity that is beyond the current debate.…”
Section: Methodsmentioning
confidence: 99%
“…Goloboff et al . (, fig. A) demonstrated that our simulated data broadly achieve their preferred measure of biological realism.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with recent work by Goloboff et al . (), we used a value of 12 for the constant of concavity ( k ) and trees were calculated through implicit enumeration. In order to achieve greater resolution at the base of the tree, the basal synapsid Dimetrodon was added to the matrix and used as the outgroup.…”
Section: Methodsmentioning
confidence: 99%